PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 011 TANJUNG PENYEMBAL - Ramadhan '; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract,. This research is Classroom Action Research (CAR), which is done to improve science learning outcomes clas IV students of SDN 011 Tanjung Penyembal with implementing cooperative learning Numbered type head together (NHT). This research was conducted on the 20th of March until the 11th of April, 2014 with two cycles. The subjects were 011 class IV students of SDN Tanjung Penyembal totaling 32 students as a source of data. This instrument is collecting on thesis observation sheet activities of teachers and students as well as student learning outcomes. Average - The average student learning outcomes before the study was of 32 students. Students who complete only the classical completeness 10 students 25%, while students who did not complete 20 people with classical completeness 75%. Because of the low student science learning outcomes it is necessary done changes in class learning environment. To improve student learning outcomes IPA performed using Cooperative learning model types numbered head together (NHT). performed two cycles seen no improvement. Teacher activity cycle increased 37.5% in the second cycle to 87.5%. Being the percentage of first cycle student activity increased 33.3% to 87.5%. on the second cycle. Student learning outcomes also increased. Average Cycle I - Average student learning outcomes of students who completed 30 of 10 people with 71.4% and the percentage of incomplete 20 people with the percentage of 28.5% In the second cycle average - average student learning outcomes of 30 students who completed 28 people with percentage of 92.8% and an incomplete only 2 people with a percentage of 71.1%. It can be concluded that to apply the Learning Model Type Cooperative Numbered Head Together (NHT) can improve learning outcomes IPA class IV students of SDN 011 Tanjung Penyembal acceptable. Keywords  : Model Study Of  Co-Operative Type of NHT, Result of Learning IPA.